Kebiasaan Makanan Ikan Tembang (Sardinella fimbriata) di Perairan Selat Sunda - Nidya Kartini (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2023)
Fringescale sardinella is a small pelagic fish in the Sunda Strait which has important ecological value. Studying fish food habits is basically to determine the quality and quantity of fish food and the ecological relationship in the tropic level. The aims of this research were to examine the food habits of fringescale sardinella in the Sunda Strait which includes the composition of the type of food, the area of ​​the niche and the overlap of the food niches. Sampling Sampling was conducted from the catch of fishermen who landed at Labuan Coastal Fishing Port, Banten. Fish samples taken during the study consisted of 620 males and 321 females. The results showed that the highest IP value was in the Thalassiothrix frauenfeldii organism, both in male (55%) and female (54%), so that Halassiothrix frauenfeldii which is a class of Bacillariophyceae was the main food for fringescale sardinella, the largest area of ​​food niches is in male was in the medium size class of 9,0028, while the largest area of ​​food niches in female was in the small size class of 8,9609, the largest overlap value of male and female food niches is in the small fish size group (101-129 mm ) with the medium fish size group (130-158 mm) were 0,9062 and 0,8105 respectively.